Implementasi Komunikasi Hybrid LoRa-WiFi pada Sistem Monitoring Level Air Berbasis IoT - Fauzan Afif (Fakultas Teknik Universitas Lampung, 2026)
Real-time water level monitoring is one of the efforts to improve the effectiveness of water resource management and reduce risks due to information delays. This study aims to develop an Internet of Things (IoT)-based water level monitoring system using hybrid LoRa–WiFi communication. This system consists of an HC-SR04 ultrasonic sensor as a water level detector, two ESP32 microcontrollers as transmitter and receiver nodes, a LoRa SX1278 module as a remote communication medium, and the Blynk IoT platform as an internet-based monitoring medium. Water level data is measured by the sensor, sent via LoRa communication to the receiver node, then forwarded to the Blynk platform via a WiFi network so that it can be monitored in real-time. Testing includes the accuracy of the ultrasonic sensor, the performance of LoRa communication on highways and open areas, and the monitoring function using Blynk IoT. The results show that this system is able to measure water levels with a good level of accuracy, communicate up to 550 m on highways and 600 m in open areas, and display water level information in real-time on the LCD and Blynk IoT. These results indicate that the developed system is capable of integrating LoRa and WiFi communications effectively, thus having the potential to be implemented as an IoT-based remote water level monitoring solution